Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To find the values for the given functions, let’s start by evaluating [tex]\( f(x) \)[/tex] at the given points and then solve the separate parts of the problem.
First, define the function:
[tex]\[ f(x) = -3x^2 + 6x - 9 \][/tex]
### Step 1: Evaluate [tex]\( f(-5) \)[/tex]
We need to substitute [tex]\( x = -5 \)[/tex] into the function:
[tex]\[ f(-5) = -3(-5)^2 + 6(-5) - 9 \][/tex]
[tex]\[ f(-5) = -3(25) + 6(-5) - 9 \][/tex]
[tex]\[ f(-5) = -75 - 30 - 9 \][/tex]
[tex]\[ f(-5) = -114 \][/tex]
### Step 2: Evaluate [tex]\( f(5) \)[/tex]
Now, substitute [tex]\( x = 5 \)[/tex] into the function:
[tex]\[ f(5) = -3(5)^2 + 6(5) - 9 \][/tex]
[tex]\[ f(5) = -3(25) + 6(5) - 9 \][/tex]
[tex]\[ f(5) = -75 + 30 - 9 \][/tex]
[tex]\[ f(5) = -54 \][/tex]
### Step 3: Compute [tex]\( f(-5) + f(5) \)[/tex]
Now add the results of [tex]\( f(-5) \)[/tex] and [tex]\( f(5) \)[/tex]:
[tex]\[ f(-5) + f(5) = -114 + (-54) \][/tex]
[tex]\[ f(-5) + f(5) = -168 \][/tex]
### Step 4: Compute [tex]\( f(-5) - f(5) \)[/tex]
Now, subtract the value of [tex]\( f(5) \)[/tex] from [tex]\( f(-5) \)[/tex]:
[tex]\[ f(-5) - f(5) = -114 - (-54) \][/tex]
[tex]\[ f(-5) - f(5) = -114 + 54 \][/tex]
[tex]\[ f(-5) - f(5) = -60 \][/tex]
Therefore, the answers are:
[tex]\[ \text{A. } f(-5) + f(5) = -168 \][/tex]
[tex]\[ \text{B. } f(-5) - f(5) = -60 \][/tex]
First, define the function:
[tex]\[ f(x) = -3x^2 + 6x - 9 \][/tex]
### Step 1: Evaluate [tex]\( f(-5) \)[/tex]
We need to substitute [tex]\( x = -5 \)[/tex] into the function:
[tex]\[ f(-5) = -3(-5)^2 + 6(-5) - 9 \][/tex]
[tex]\[ f(-5) = -3(25) + 6(-5) - 9 \][/tex]
[tex]\[ f(-5) = -75 - 30 - 9 \][/tex]
[tex]\[ f(-5) = -114 \][/tex]
### Step 2: Evaluate [tex]\( f(5) \)[/tex]
Now, substitute [tex]\( x = 5 \)[/tex] into the function:
[tex]\[ f(5) = -3(5)^2 + 6(5) - 9 \][/tex]
[tex]\[ f(5) = -3(25) + 6(5) - 9 \][/tex]
[tex]\[ f(5) = -75 + 30 - 9 \][/tex]
[tex]\[ f(5) = -54 \][/tex]
### Step 3: Compute [tex]\( f(-5) + f(5) \)[/tex]
Now add the results of [tex]\( f(-5) \)[/tex] and [tex]\( f(5) \)[/tex]:
[tex]\[ f(-5) + f(5) = -114 + (-54) \][/tex]
[tex]\[ f(-5) + f(5) = -168 \][/tex]
### Step 4: Compute [tex]\( f(-5) - f(5) \)[/tex]
Now, subtract the value of [tex]\( f(5) \)[/tex] from [tex]\( f(-5) \)[/tex]:
[tex]\[ f(-5) - f(5) = -114 - (-54) \][/tex]
[tex]\[ f(-5) - f(5) = -114 + 54 \][/tex]
[tex]\[ f(-5) - f(5) = -60 \][/tex]
Therefore, the answers are:
[tex]\[ \text{A. } f(-5) + f(5) = -168 \][/tex]
[tex]\[ \text{B. } f(-5) - f(5) = -60 \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.